IMPLEMENTASI KEBIJAKAN PENGENDALIAN PENCEMARAN AIR SUNGAI WINONGO AKIBAT LIMBAH DOMESTIK DI KOTA YOGYAKARTA - Puji Prikhatna; Fransisca Romana Harjiyatni; Sunarya Raharja (Kajian Hukum, 2022)
Rivers are the main water providers for humans. By making it the most important water provider, this has a negative impact on the river. Pollution of river water in the city of Yogyakarta is quite heavy. Pollution of the Watershed (DAS) is quite severe, at least found in the Winongo River Watershed, Yogyakarta City. The purpose of this research was to identify and analyze the implementation of the Winongo River water pollution control policy due to domestic waste and the implementation factors for controlling Winongo River water pollution control policy due to domestic waste. The location of this research is in the city of Yogyakarta. Data collection techniques used are literature studies, document studies, interviews. The results of research on controlling Winongo River water pollution due to domestic waste in the City of Yogyakarta show that the implementation of the policy to control Winongo River water pollution due to domestic waste in the City of Yogyakarta by the Yogyakarta City Environmental Service has been going well, even though in 2021 it has not been implemented optimally.